Криміналістична характеристика створення та поширення контенту з вмістом дитячої порнографії з використанням інформаційно-телекомунікаційних систем або технологій - Книженко, С. О.; Knyzhenko, S. O.; ORCID: http://orcid.org/0000-0002-1944-4256 (Аналітично-порівняльне правознавство. - 2022. - № 3. - С. 227-231, 2022)
Визначено криміналістичну характеристику створення та поширення контенту з вмістом дитячої порнографії з використанням інформаційно-телекомунікаційних систем або технологій. Вказаний вид кримінальних правопорушень віднесено до комплексних методик. Зазначено, що створення та поширення контенту зі вмістом дитячої порнографії з використанням інформаційно-телекомунікаційних систем або технологій вчиняються найчастіше організованими злочинними угрупуваннями з корисливих мотивів, які мають у собі чітку ієрархічну структуру: організатор; вербувальники; режисери; виконавці; розповсюджувачі порнографічного контенту. Особливістю обстановки вчинення досліджуваної групи кримінальних правопорушень є те, що місце вчинення сексуального насильства (тобто створення контенту зі вмістом дитячої порнографії) має конкретну (фізичну) адресу, а поширення такого контенту вчиняється з використанням інформаційно-телекомунікаційних систем або технологій.

The article is devoted to the forensic characteristics of the creation and distribution of content containing child pornography using information and telecommunication systems or technologies. This type of criminal offenses is classified as complex methods. The components of criminal technology are: obtaining access to child pornography, its acquisition, storage, importation, transportation or other movement, production, sale and distribution (Article 301-1 of the Criminal Code of Ukraine); rape (Article 152 of the Criminal Code of Ukraine); committing acts of a sexual nature with a person who has not reached the age of sixteen (Article 155 of the Criminal Code of Ukraine); sexual violence (Article 153 of the Criminal Code of Ukraine); corruption of minors (Article 156 of the Criminal Code of Ukraine); human trafficking (Article 149 of the Criminal Code of Ukraine). Girls aged 9 to 13 were most often involved in the creation of sexual content. Criminals take advantage of the vulnerable state of children, caused by the fact that they have not yet formed sexual identification, hierarchy of motives, moral consciousness and self-awareness. In more than 90% of cases, the investigated crimes were committed with the participation of persons close to the child. Such criminal offenses are committed for sexual and selfish motives. Consumers of pornographic content have a sexual motive. The creation and distribution of content containing child pornography using information and telecommunication systems or technologies is most often committed by organized criminal groups for selfish motives, which have a clear hierarchical structure: the organizer; recruiters; directors; performers; distributors of pornographic content. Criminal technologies include two groups of offenses: 1) actions related to violence against a child; 2) actions related to the creation and distribution of pornographic content using information and telecommunication systems or technologies. The peculiarity of the circumstances of the commission of the investigated group of criminal offenses is that the place of sexual violence (that is, the creation of content containing child pornography) has a specific (physical) address, and the distribution of such content is carried out using information and telecommunication systems or technologies. Criminal technologies include two groups of offenses: 1) actions related to violence against a child; 2) actions related to the creation and distribution of pornographic content using information and telecommunication systems or technologies. The peculiarity of the circumstances of the commission of the investigated group of criminal offenses is that the place of sexual violence (that is, the creation of content containing child pornography) has a specific (physical) address, and the distribution of such content is carried out using information and telecommunication systems or technologies.

Определена криминалистическая характеристика создания и распространения контента с содержанием детской порнографии с использованием информационно-телекоммуникационных систем или технологий. Указанный вид уголовных правонарушений отнесен к комплексным методикам. Отмечено, что создание и распространение контента с содержанием детской порнографии с использованием информационно-телекоммуникационных систем или технологий совершаются чаще всего организованными преступными группировками по корыстным мотивам, которые содержат четкую иерархическую структуру: организатор; вербовщики; режиссеры; исполнители; распространители порнографического контента. Особенностью обстановки совершения исследуемой группы уголовных правонарушений является то, что место совершения сексуального насилия (т.е. создание контента с содержанием детской порнографии) имеет конкретный (физический) адрес, а распространение такого контента осуществляется с использованием информационно-телекоммуникационных систем или технологий.
Forensic characteristics of the creation and distribution of content containing child pornography using information and telecommunications systems or technologies
Книженко, С. О. Криміналістична характеристика створення та поширення контенту з вмістом дитячої порнографії з використанням інформаційно-телекомунікаційних систем або технологій [Електронний ресурс] / Книженко С. О. // Аналітично-порівняльне правознавство. - 2022. - № 3. - С. 227-231. - Режим доступу : http://app-journal.in.ua/wp-content/uploads/2022/09/42.pdf.
Keywords: Криміналістика. Criminalistics. Криминалистика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; криміналістична характеристика; criminalistical characteristics; криминалистическая характеристика; створення та поширення контенту з вмістом дитячої порнографії; creation and distribution of content containing child pornography; создание и распространение контента с содержанием детской порнографии; комп’ютерні технології; computer technology; компьютерные технологии; шкідливий контент; harmful content; вредоносный контент; криміналістична методика; forensic technique; криминалистическая методика; захист прав дітей; protection of children's rights; защита прав детей; порнографічна продукція; pornographic products; порнографическая продукция